Kearifan lokal masyarakat dalam menjaga kelestarian padang rumput Kebar di Distrik Kebar - Marthinus Anari; Nouke Lenda Mawikere; Meike M. Lisangan (Cassowary, 2023)
The existence of the Kebar prairie in Kebar District, Tambrauw Regency is guarded by every subtribe or clan of the Kebar community without writing which must be obeyed by every member of the tribe. The aims of this study were (1) to identify the behavior and public perception of the Kebar grass based on the local wisdom (Bafirombar Bitoro) and (2) to find out the views or orientations of the cultural values of the Kebar people on how to protect and preserve the environment, especially in the Kebar grasslands. This research was carried outs using a survey research method. Respondents consisted of 55 household heads from Jandura and Anjai villages, as well as key informants (tribal heads, religious leaders such as pastors, village heads, district officials or PPL, and the police). The results showed that the Kebar people who live in the Kebar prairie have a strong relationship or relationship with the Kebar grass in their daily life. The Kebar community also has cultural values about the efforts to maintain a good harmony with the natural surroundings, especially in preserving Kebar grass.